SISTEM PENAKARAN AIR UNTUK PROSES PEMBUATAN ADONAN ROTI - Aidi Finawan (Politeknik Negeri Lhokseumawe, 2014)
Scale of water for industrial bread dough on a household scale is still done manually, measured with a graduated container. Failures bread making process are often caused by inappropriate dosage of water needs due to the negligence of the workers.. Therefore, it is necessary to figure out how to control the dosing of water easily to the dough that is accordance to the composition of flour needed. This research showed a water dosing system for dough bread flour depending on the needs of the composition. A graduated system of the water can be applied to the bread maker mixer and can be used for both at home scale or bakery industry. The mean error in testing showed frm 0,0040% to 0,0059% choice for bread and sweet bread choice. Both of these values showed low percentage of mistakes,and it can be concluded that a graduated system can be applied to a graduated water in the process of making bread dough